Integritas Personal dan Kepemimpinan Etis - Gea, Antonius Atosökhi (Bina Nusantara University, 2014)
Integrity is very important for a leader. When a leader does not have integrity, then, sooner or later it will destroy the group or organization s/he leads. This occurs because the policies, decisions, attitudes, and actions made by the leader will have wide impact to the organization. A leader will be the center of attention of the members, and whatever they see in her/him will have a huge impact on the organization as a whole. Integrity has been given a lot of meaning; and everything is interconnected, which essentially refers to one's personal qualities, which make a person trustworthy and reliable. In the world of work, integrity appears in the form of good work performance or results. To be able to produce a good performance it is necessary to have competence. With integrity possessed the competence can be directed to produce a good performance. The problem that occurs is a lack of understanding of the relationship between integrity and performance. Generally, they are both understood separately, as stand-alone. But in reality the integrity is manifested through good performance. This applies also to a leader, which results a good performance in implementing ethical leadership. The purpose of this paper is to outline the relationship between integrity and performance, in which competence plays an important role. Integrity is the foundation for leadership, which makes it able to run and produce ethical leadership performance.